Pendidikan Islam Inklusif Multikulutural dalam Perspektif Al Quran di Madrasah - Nurfadillah, Annisa; Albina, Meyniar (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Multicultural inclusive Islamic education is a strategic approach in facing the challenges of diversity in Indonesian society. This article aims to examine how the values of inclusivity and multiculturalism in the perspective of the Qur'an can be applied in madrasahs. This study uses a descriptive qualitative method with a literature study approach to the verses of the Qur'an, educational policies, and previous research results. The results of the study show that the principle of inclusivity taught in the Qur'an, such as in Surah Al-Hujurat verse 13, is the main foundation for creating a curriculum that respects cultural, religious, and special needs diversity. This approach is not only relevant to improving the quality of learning, but also to forming the character of students who are tolerant, fair, and harmonious. The implementation of multicultural inclusive Islamic education in madrasahs requires the support of a holistic curriculum, teacher training, and a school culture that respects diversity. This article emphasizes the importance of synergy between theological values and educational practices in realizing a peaceful society amidst diversity.